Influence of Diabetes Mellitus on myocardial repolarization by measurement of QT variability Index - Al-Hashimi, Abbas F.; Mohammed, Najeeb H.; Thamer, Ammar A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Various abnormalities in myocardial repolarization assessed by QT variability index (QTVI) in diabetics are associated with high risk to ventricular arrhythmia. The increase in cardiovascular morbidity and mortality appears to relate to the synergism of hyperglycemia with dyslipidemia, hypertension and obesity in addition to disturbed myocardial repolarization.Objectives: The aim of the present study was to estimate and evaluate an index of myocardial repolarization instability (QTVI) in patients with DM on insulin or oral hypoglycemic drugs in comparison with healthy individuals.Patients and Methods: The study was conducted on fifty six (56), middle-aged patients with DM of either sex in addition to age-matched healthy subjects (32) served as control, during the period between December 2009 to January 2011 in Al-Kadhimya Hospital. 21 patients were on insulin therapy and 35 were on oral hypoglycemic drugs (OHD). Holter monitoring for 30 minutes was performed for each subject, and QTVI was calculated as the logarithm of the ratio between the variances of the normalized QT and RR intervals.Results: QTVI was significantly increased in patients with DM as compared with the control healthy subjects (−0.82± 0.56, −1.54± 0.27 respectively; P